Free market criminal justice : how democracy and laissez faire undermine the rule of law - Brown, Darryl K. (New York, NY : Oxford University Press, 2016)
'Free Market Criminal Justice' explains how excessive faith in democratic politics and free markets has undermined the rule of law in U.S. criminal process.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 14, 2015).
Keywords: Criminal justice, Administration of -- United States; Plea bargaining -- United States; Law and economics; True Crime